Hermeneutika Hadis Menurut Muhammad Iqbal: Kajian Teoretis dan Implikasinya pada Era Kontemporer - Adnan; Musahadi; Nisrin Mu'azzaz (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2026)
This study explores Muhammad Iqbal’s philosophical contribution to Hadith hermeneutics through his synthesis of tradition and modernity. Iqbal views the Hadith as a living tradition that engages with human reason and social transformation rather than a static legal text. His thought emphasizes the unity of sanad and matn, the dynamic principle of ijtihad, and the balance between spiritual authenticity and contextual relevance. Drawing on